KEGAGALAN TOKOH UTAMA DALAM USAHA MENEMUKAN IDENTITAS DIRI PADA FILM YUNI - Aini, Eka Nur; Pratiwi, Yuni (Hiski Malang, 2023)
Self-identity is one of the most important things for a person. Nowadays, it is not uncommon for teenagers to fail in finding their self-identity. One of the movies that contains the failure of teenagers in finding self-identity is the movie Yuni. This study aims to describe the form of failure of the main character in the movie Yuni. This research is a qualitative research using descriptive method. The data used in this study are in the form of dialog between characters and pieces of images that are in accordance with the focus of the research. The data source in this research is the movie Yuni which was released in 2021 and directed by Kamila Andini. This research uses the theory of literary sociology and literary picology. Based on the results of the analysis, three conclusions were obtained about the form of the character's failure in finding self-identity, namely (1) failure to understand customs, including failing to understand the meaning of myths believed by the surrounding community, (2) failure in modern life, including being closed, unable to master and use technological flows positively, and unable to manage challenges, and (3) failure in finding self-identity, including choosing the wrong figure as an example, weak personality, and having a narrow view of life.